Physical exercise in aging human skeletal muscle increases mitochondrial calcium uniporter expression levels and affects mitochondria dynamics. Issue 24 (30th December 2016) - Zampieri, Sandra; Mammucari, Cristina; Romanello, Vanina; Barberi, Laura; Pietrangelo, Laura; Fusella, Aurora; Mosole, Simone; Gherardi, Gaia; Höfer, Christian; Löfler, Stefan; Sarabon, Nejc; Cvecka, Jan; et al.
Abstract: Age‐related sarcopenia is characterized by a progressive loss of muscle mass with decline in specific force, having dramatic consequences on mobility and quality of life in seniors. The etiology of sarcopenia is multifactorial and underlying mechanisms are currently not fully elucidated. Physical exercise is known to have beneficial effects on muscle trophism and force production. Alterations of mitochondrial Ca 2+ homeostasis regulated by mitochondrial calcium uniporter (MCU) have been recently shown to affect muscle trophism in vivo in mice. To understand the relevance of MCU‐dependent mitochondrial Ca 2+ uptake in aging and to investigate the effect of physical exercise on MCU expression and mitochondria dynamics, we analyzed skeletal muscle biopsies from 70‐year‐old subjects 9 weeks trained with either neuromuscular electrical stimulation (ES) or leg press. Here, we demonstrate that improved muscle function and structure induced by both trainings are linked to increased protein levels of MCU. Ultrastructural analyses by electron microscopy showed remodeling of mitochondrial apparatus in ES‐trained muscles that is consistent with an adaptation to physical exercise, a response likely mediated by an increased expression of mitochondrial fusion protein OPA1. Altogether these results indicate that the ES‐dependent physiological effects on skeletal muscle size and force are associated with changes in mitochondrial‐related proteins involved in Ca 2+ homeostasis and mitochondrial shape. These original findings in aging human skeletal muscle confirm the data obtained in mice and propose MCU and mitochondria‐related proteins as potential pharmacological targets to counteract age‐related muscle loss. Abstract : Nine weeks of physical exercise in sedentary elderlies resulted in an increase in muscle torque and strength and in the maintenance of muscle fiber size, likely mediated by increased expression levels of MCU and OPA1‐mediated mitochondria adaptation. We propose mitochondria as the sensors of physical activity that can retrogradely activate nuclear programs to regulate muscle mass. These results provide an effective ES protocol of training and identify mitochondrial proteins regulating Ca 2+ uptake and structural remodeling as new targets to develop therapeutic strategies counteracting sarcopenia and promoting healthy aging.